A systematic review of concussion in rugby league. Issue 8 (10th April 2014) - Gardner, Andrew; Iverson, Grant L; Levi, Christopher R; Schofield, Peter W; Kay-Lambkin, Frances; Kohler, Ryan M N; Stanwell, Peter
Abstract : Objectives: Concussion remains one of the inherent risks of participation in rugby league. While other injuries incurred by rugby league players have been well studied, less focus and attention has been directed towards concussion. Review method: The current review examined all articles published in English from 1900 up to June 2013 pertaining to concussion in rugby league players. Data sources: Publications were retrieved via six databases using the key search terms: rugby league, league, football; in combination with injury terms: athletic injuries, concussion, sports concussion, sports-related concussion, brain concussion, brain injury, brain injuries, mild traumatic brain injury, mTBI, traumatic brain injury, TBI, craniocerebral trauma, head injury and brain damage. Observational, cohort, correlational, cross-sectional and longitudinal studies were all included. Results: 199 rugby league injury publications were identified. 39 (20%) were related in some way to concussion. Of the 39 identified articles, 6 (15%) had the main aim of evaluating concussion, while the other 33 reported on concussion incidence as part of overall injury data analyses. Rugby league concussion incidence rates vary widely from 0.0 to 40.0/1000 playing hours, depending on the definition of injury (time loss vs no time loss). The incidence rates vary across match play versus training session, seasons (winter vs summer) and playing position (forwards vs backs). The ball carrier has been found to be at greater risk for injury than tacklers. Concussion accounts for 29% of all injuries associated with illegal play, but only 9% of injuries sustained in legal play. Conclusions: In comparison with other collision sports, research evaluating concussion in rugby league is limited. With such limited published rugby league data, there are many aspects of concussion that require attention, and future research may be directed towards these unanswered questions.